IMPACT OF DIVERSIFICATION ON AGRICULTURAL PRODUCTIVITY (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Agriculture is an extremely important strategic network in the economic, social and environmental stability of any country. It performs tasks such as providing the population with food, promoting export potential, ensuring employment in rural areas and maintaining a certain share in the country's GDP. Therefore, the development of the agricultural sector is decisive not only in ensuring food security, but also in maintaining socio-economic balance.